The Effect Of Media Composition On The Growth Of Angsana (Pterocarpus Indicus) (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2024)
The purpose of this research was to find out the Influence of the Composite of the Planting Media on the Growth of Angsana Plant and the composition of a good plant media for Angsana plantation. This research uses a single Design (DK) factor, with a medium dose treatment of M0 = Topsoil Each Polybag, M1 = Media 100 Gram Each Polybag, M2 = Media 200 Gram Each Polybag, M3 = Media 300 Gram Each Polybag. As a result, it will continue to be analyzed using the DMRT (Duncan Multiply Class Test) tasks 95% with the application of Statistics tools for Agriculture Research. The length of plant observation, for treatment with less control in each unit with a value of (A0) of 19.33cm, has no significant influence on the treatment of each unit. In addition to treatment (A1) 10 Treatment by (A3) 100.33cm and (A3) 40.33cm had a significant influence on treatment (A0) 19.33cm. of treatment A1, A3 and A2 showed that the influence of organic breastfeeding or animal waste on the supply of Angsana plants increased in length or height in each unit.